Unravelling the origin of the common wall lizards (Podarcis muralis) in south-eastern Europe using mitochondrial evidence - Oskyrko, Oleksandra; Sos, Tibor; Vacheva, Emiliya; Vlad, Sabina E.; Cogălniceanu, Dan; Uller, Tobias; Feiner, Nathalie; Carretero, Miguel A. (Biodiversity Data Journal, 2022)
The origin of the common wall lizards (Podarcis muralis) populations in south-eastern Europe (namely in Bulgaria and Romania), representing the north-eastern range border of this species, was addressed using mitochondrial DNA. We compared cytochrome b sequences from Bulgaria and Romania with those from the contiguous range in Central Europe that are available from previous studies. We recorded five main haplogroups in Bulgaria and Romania, belonging to the Central Balkan clade. However, haplogroup III was recorded in more localities than previously found. Additionally, signs of haplotype admixture were identified in several populations along the Danube River. The presence of the Southern Alps haplotype in one population from Otopeni, Bucharest (Romania) and its close phylogenetic relationships to north Italy populations suggests human-mediated introductions of this wall lizard clade in Romania. Our results confirm that P.
Keywords: Eastern europe; Genetic diversity; Introduction; Lacertidae; Phylogeography